2015
DOI: 10.1590/s0034-8910.2015049006058
|View full text |Cite
|
Sign up to set email alerts
|

Methods and challenges for the health impact assessment of vaccination programs in Latin America

Abstract: OBJECTIVE To describe methods and challenges faced in the health impact assessment of vaccination programs, focusing on the pneumococcal conjugate and rotavirus vaccines in Latin America and the Caribbean.METHODS For this narrative review, we searched for the terms “rotavirus”, “pneumococcal”, “conjugate vaccine”, “vaccination”, “program”, and “impact” in the databases Medline and LILACS. The search was extended to the grey literature in Google Scholar. No limits were defined for publication year. Original art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…As reported in the literature [65], our results shows that most studies on impact of public health interventions used secondary data from health information systems, surveillance systems, and others sources, while few studies used primary data. As hospitalization and mortality outcomes are the most relevant outcomes of interest, it is expected that secondary data are the most used data sources.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…As reported in the literature [65], our results shows that most studies on impact of public health interventions used secondary data from health information systems, surveillance systems, and others sources, while few studies used primary data. As hospitalization and mortality outcomes are the most relevant outcomes of interest, it is expected that secondary data are the most used data sources.…”
Section: Discussionmentioning
confidence: 52%
“…On the other hand, effectiveness measurements based on observational study designs, such as cohort and case-control studies, estimated the proportion of cases prevented in vaccinated subjects that were attributable to vaccination excluding indirect effects. A recent study describing methods and challenges for impact assessment of vaccination in LAC region reported a significant increase in the number of studies on pneumococcal vaccine impact [65]. As other authors have reported in developed countries [64], several are the methodological challenges faced when assessing vaccination impact, particularly considering PCV.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of PHiD-CV against IPD has also been estimated in Brazil, Chile, and Colombia using data collected by the Latin American laboratory network for passive surveillance of bacterial pneumonia and meningitis pathogens (SIREVA II) [16]. While these data provide useful information on serotype distribution during particular periods of time, caution is advised in the analysis of the impact of vaccination since SIREVA II is a voluntary system and completeness of reporting varies among countries [17]. Analyses of the laboratory-based data are also limited by a lack of demographic and clinical information.…”
Section: What Is the Context?mentioning
confidence: 99%
“…160 The use of IIS is a promising tool useful for both vaccine providers and vaccine recipients as well as public health policy makers and epidemiologists. 13,161 It allows access to flexible analyses that cannot be done using other vaccination data sources. It is able to reduce the burden of manual paper reporting systems, to facilitate quarterly vaccine coverage reports instead of aggregate data, to increase the accuracy of the data and to track the administered doses.…”
Section: Resultsmentioning
confidence: 99%